ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT MAHASISWA AKUNTANSI UNTUK MENGIKUTI PENDIDIKAN PROFESI AKUNTANSI DITINJAU DARI GENDER DAN STATUS AKREDITASI PROGRAM STUDI - Edy Suprianto; Mifkhatun Nikmahi (Jurnal Akuntansi Indonesia, 2013)
The purpose of this research to analyze the influence of career motivation, motivational qualities, economic motivation, motivation degree, the motivation to follow Certification Exam Certified Public Accountants, the cost of education and a long interest in the education of accounting students to follow the Accounting Profession. Population in this research that students majoring in accounting at a private college in Semarang, purposive sampling technique used for sample retrieval and obtained a sample of 50 respondents, the data analysis techniques used multiple linear regression. These results indicate that the economic motivation, motivation and motivation to follow quality Certification Exam Certified Public Accountants significantly influence accounting students’ interest to follow Accounting Profession. Career motivation, degree of motivation, education costs and length of education did not significantly affect student interest in accounting to follow the Accounting Profession. Other results showed that no significant differences in student interest in accounting to follow the Accounting Profession in terms of gender, and there is also no significant difference in student interest in accounting to follow the Accounting Profession in terms of accreditation status